2005
DOI: 10.1007/s00146-005-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Meetings and meeting modeling in smart environments

Abstract: In this paper we survey our research on smart meeting rooms and its relevance for augmented reality meeting support and virtual reality generation of meetings in real time or off-line. The research reported here forms part of the European 5th and 6th framework programme projects multi-modal meeting manager (M4) and augmented multi-party interaction (AMI). Both projects aim at building a smart meeting environment that is able to collect multimodal captures of the activities and discussions in a meeting room, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…The Human Media Interaction (HMI) group of the University of Twente is one of the AMI partners (Nijholt et al 2004). The HMI group has a tradition in research into interaction with embodied conversational agents, computer graphics for virtual environments and machine learning techniques for recognition of higher level features (e.g., dialogue acts, gestures and emotions) from lower level features (e.g., words, hand movements and facial features).…”
Section: Introductionmentioning
confidence: 99%
“…The Human Media Interaction (HMI) group of the University of Twente is one of the AMI partners (Nijholt et al 2004). The HMI group has a tradition in research into interaction with embodied conversational agents, computer graphics for virtual environments and machine learning techniques for recognition of higher level features (e.g., dialogue acts, gestures and emotions) from lower level features (e.g., words, hand movements and facial features).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the area of smart meeting systems provides another set of examples of technologies that act to support participants in meetings by automatically analyzing the group behavior [15,20]. For example, Pianesi et al [18] have shown that multimodal information from meeting participants can be used to model the group dynamics and to generate post-activity summary reports that can help participants to improve their awareness on the meeting performance.…”
Section: Related Workmentioning
confidence: 99%
“…In the context of our work, we strive to develop an application to be operated in a smart meeting room (smart lab in our university). Smart meeting rooms are a specific subset of smart environments where the main goal is the beneficial exchange of information among the resident users (Nijholt et al, 2004). Several requirements have to be fulfilled by the desired application in order to achieve the optimal conceivable assistive system which then leads to the user's satisfaction with the environment.…”
Section: Introductionmentioning
confidence: 99%